Before Hospice: Symptom Burden, Dementia, and Social Participation in the Last Year of Life - Amjad, Halima (J Palliat Med, 2019)
Background: Little is known about clinical symptom burden, dementia, and social isolation in the last year of life among older adults. Objective: To describe and contrast the type and severity of symptom burden for older decedents with and without dementia, and whether specific symptoms and presence of dementia are associated with limitations in social participation in the last year of life. Design: Cross-sectional logistic regression analysis of a population-based study. Setting/Subjects: A total of 1270 community-dwelling adults of age ≥65 years in the United States participated in the 2011 National Health and Aging Trends Study and died by 2015. Measurements: Dementia status, 13 clinical symptoms, and limitations in 6 social activities were drawn from the interview preceding death. Severity of sensory, physical, and psychiatric symptom burden was examined in tertiles. Results: Decedents with dementia (37.3%) had higher prevalence of all symptoms (p's < 0.05), except insomnia and breathing problems. Dementia was associated with greater likelihood of high versus low burden of sensory (odds ratio [OR] 4.52 [95% confidence interval CI 3.08–6.63]), physical (OR 3.49 [95% CI 2.48–4.91]), and psychiatric (OR 2.80 [95% CI 1.98–3.95]) symptoms. Dementia and physical symptoms (problems with speaking, leg strength/movement, and balance) were independently associated with limitations in at least three social activities (p's < 0.05 for adjusted ORs). Conclusion: Symptom burden is higher in patients with dementia. Dementia and physical symptoms are associated with social activity limitations. Older patients with dementia or physical symptoms may benefit from earlier emphasis on palliative care and quality of life.